The The Effectiveness of Sharia Financing in BMD Syariah on the Development of MSMEs - Adela Ulifatul Ulfa; Anisa Hilmi Fuadah; Friska Dwi Yulina (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to analyze the effectiveness of sharia financing implemented by BMD Syariah in supporting the development of Micro, Small, and Medium Enterprises (MSMEs). The background of this research is based on the community's need for access to financing that is fair, usury-free, and in accordance with sharia principles, especially for lower economic groups that have not been reached by formal financial institutions. The research method used is qualitative descriptive with a field study approach through observation, interviews, and documentation. The results of the study show that sharia financing in BMD Syariah, through the Murabahah, Mudharabah, Ar-Rahn, and Al-Ijarah contracts, has proven to be effective in increasing business capacity, income, and welfare of MSME actors. However, there are still challenges in the form of low Islamic financial literacy and the risk of problematic financing. This study concludes that BMD Syariah has a strategic role in encouraging financial inclusion and community economic empowerment based on sharia values.